Negative Attitudes, Network and Education - Patrick Bennett; Lisbeth La Cour; Birthe Larsen; Gisela Waisman (Copenhagen Business School (CBS), Department of Economics, 2015)
This paper explores potential explanations behind the educational gap between young natives and immigrants using two measures, negative attitudes towards immigrants and networking, which may influence natives and immigrants differently. The paper considers, both theoretically and empirically, the impact of negative attitudes and networking taking into account that these parameters may influence high and uneducated workers as well as immigrants and natives differently, creating different incentives to acquire education for the two ethnic groups. Using rich Danish administrative data, this paper finds evidence that greater negative attitudes increase incentives for males to acquire education and that networking also increases immigrant education.
hdl:10398/9153
Keywords: I20; I24; J15; 330; incentives; immigrants; education; attitudes